Store Atmosphere, Diskon Harga dan Impulse Buying: Peran Mediasi Positive Emotion dalam Konteks Pengalaman Belanja - Nel Arianty; Adek Devira Purba (JURNAL ILMIAH MANAJEMEN & BISNIS, 2023)
ABSTRACTPurpose – To identify the influence of Store Atmosphere, Price Discounts, impulse buying, Store Atmosphere and Price Discounts on Positive Emotions and to explore the mediating role of positive emotions in this relationship.Method – The sampling technique uses non-probability sampling with purposive sampling technique, and data is collected using a questionnaire from 96 respondents who filled out the questionnaire. The data analysis technique uses Structural Equation Modeling - Part Least Square (SEM-PLS).Findings –  The research results prove that Store atmosphere and Price discounts influence impulse buying, Store atmosphere and Price discounts influence Positive emotions, and Positive emotions influence impulse buying. Positive emotions are proven to mediate the influence between Store atmosphere and Price discounts.Originality/Novelty –  This research provides added value by highlighting the critical role of Positive emotion as a driver of impulse buying in the context of Indomaret Fresh consumers. These findings open up the potential for new marketing strategies that create shopping experiences that evoke positive emotions.Implications – The findings of this research can provide strategic guidance for Indomaret Fresh management to improve consumer shopping experiences by paying attention to store atmosphere, price, and the importance of creating positive emotions to encourage impulse purchases. These implications can also be helpful for further research in retail marketing.